2020
DOI: 10.1021/acsami.0c10699
|View full text |Cite
|
Sign up to set email alerts
|

Protein Component of Oyster Glycogen Nanoparticles: An Anchor Point for Functionalization

Abstract: Bio-sourced nanoparticles have a range of desirable properties for therapeutic applications, including biodegradability and low immunogenicity. Glycogen, a natural polysaccharide nanoparticle, has garnered much interest as a component of advanced therapeutic materials. However, functionalizing glycogen for use as a therapeutic material typically involves synthetic approaches that can negatively affect the intrinsic physiological properties of glycogen. Herein, the protein component of glycogen is examined as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The result shows that the radial density reaches maximum close to the center of glycogen particles, which is consistent with random growth pattern of glycogen particles ( Zhang et al, 2018 ). Even more recent work by Besford et al (2020) has again shown these same density distributions (pair-distance distributions) for commercial glycogen beta particle preparations that matches the density observed previously.…”
Section: Glycogen β Articlessupporting
confidence: 84%
See 1 more Smart Citation
“…The result shows that the radial density reaches maximum close to the center of glycogen particles, which is consistent with random growth pattern of glycogen particles ( Zhang et al, 2018 ). Even more recent work by Besford et al (2020) has again shown these same density distributions (pair-distance distributions) for commercial glycogen beta particle preparations that matches the density observed previously.…”
Section: Glycogen β Articlessupporting
confidence: 84%
“… Powell et al (2015) studied size change of glycogen α particles in liver glycogen and phytoglycogen via acid hydrolysis, according to which, formation of α particles in liver glycogen might be due to the linkage of β particles via covalent or strong non-covalent bonds involving proteins. Recently, Besford et al (2020) shows that glycogen particle sizes and shapes change in the presence of protease enzymes that removes proteins from the particles, which reflects that reduction in surface-bound protein leads to the potential cleavage of alpha particles. However, it is currently not clear which protein(s) are involved in glycogen α particle formation.…”
Section: Molecular Mechanisms Of Glycogen α-Particle Formation and Fragilitymentioning
confidence: 99%
“…The protein content per mass of glycogen nanoparticle was found to be 8 μg/mg for OG, 5.3 μg/mg for BG, 2.9 μg/mg for RG and 1.6 μg/mg for PG [ 32 ]. Previous studies suggest that the protein component of glycogen may be either incorporated within the structure and/or situated on the surface of the particles [ 32 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The protein content per mass of glycogen nanoparticle was found to be 8 μg/mg for OG, 5.3 μg/mg for BG, 2.9 μg/mg for RG and 1.6 μg/mg for PG [ 32 ]. Previous studies suggest that the protein component of glycogen may be either incorporated within the structure and/or situated on the surface of the particles [ 32 , 36 ]. We have recently shown that the protein component of OG can be exploited as an anchor point for the photopolymerization of poly( N -isopropylacrylamide) chains on the surface of glycogen nanoparticles [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The outer surface of GNPs is highly branched and has a dense inner core. Because of their high hydrophilicity and biocompatibility, they can easily be biochemically modified to produce functional derivatives [ 198 ], such as adhesive GNPs composed of lipoate-conjugated phytoglycogen (L-PG) [ 199 ] and oyster GNPs with poly(N-isopropylacrylamide) (PNIPAM) chains on their surface [ 200 ].…”
Section: Np Delivery—a Platform Ensuring the Efficacy And Stability O...mentioning
confidence: 99%